Spinning Silver - Novik, Naomi (New York : Del Rey, 2018)
"Miryem is the daughter and granddaughter of moneylenders, but her father is not a very good one. Free to lend and reluctant to collect, he has left his family on the edge of poverty--until Miryem intercedes. Hardening her heart, she sets out to retrieve what is owed, and soon gains a reputation for being able to turn silver into gold. But when an ill-advised boast brings her to the attention of the cold creatures who haunt the wood, nothing will be the same again. For words have power, and the fate of a kingdom will be forever altered by the challenge she is issued"--
Keywords: Rumpelstiltskin (Folk tale) -- Adaptations; Fiction; Moneylenders; Fiction; Young women; Fiction; Kings and rulers; Fiction; Secrecy; Fiction; Quests (Expeditions); Fiction; Fantasy fiction; Fantasy; Fantasy fiction; Fantasy fiction